Auction of Confiscated Assets by the Corruption Eradication Commission (KPK) at the Investigation Stage from the Perspective of the Presumption of Innocence - Herusantoso, Bayu Praditya; Ahmadi, Ali; Maulana, Bino Aldy (Journal of Contemporary Law Studies, 2024)
This study examines the procedures for auctioning confiscated assets by the Corruption Eradication Commission (KPK) during the investigation stage and their implications on the rights of suspects from the perspective of the presumption of innocence principle. The method used is normative juridical with a regulatory approach, using secondary data from legal documents and relevant literature. The findings indicate that the auction procedures for confiscated assets are regulated under Government Regulation Number 105 of 2021, covering stages such as preparation, execution, winner determination, asset transfer, and proceeds management. These procedures generally align with the presumption of innocence principle, incorporating measures to ensure suspects' rights are not violated, such as notification and approval from suspects or their representatives, and transparency in the auction process. However, practical challenges such as public perception and the condition of confused assets require further attention. The legal implications include the protection of property rights, the right to justice, and the right to a fair legal process. Recommendations for improving procedures include enhancing coordination with auction officials, providing detailed notification mechanisms, and thorough verification and evaluation of assets.